Effect of the number of screws on the stability of locking mandibular reconstruction plates - Pereira-Filho, V. A. [UNESP]; Da Silva, B. N. [UNESP]; Nunes Reis, J. M. [UNESP]; Spin-Neto, R. [UNESP]; Real Gabrielli, M. F. [UNESP]; Monnazzi, M. S. [UNESP] (Elsevier, 2013)
Atrophic mandible fractures are frequently a challenge to stabilize. This study evaluated, through mechanical testing in vitro, the number of locking screws that is sufficient to withstand loading when applied with a locking reconstruction plate in the fixation of atrophic mandible fractures. Polyurethane mandibles with a simulated linear fracture at the midline were used as substratum. Results show that resistance of the fixation is poor when one and two screws are used on each side of the fracture. Three screws on each side of the fracture significantly increases the resistance to displacement. However, no additional strength is added to the construct when more than three screws per side are used. © 2013 International Association of Oral and Maxillofacial Surgeons.
Keywords: atrophic mandible; edentulous mandible; mandibular fracture; polyurethan; bone plate; controlled study; fracture fixation; human; in vitro study; locking screw; mandible fracture; mandible reconstruction